KOMPETENSI SOSIAL PENDIDIK DALAM ALQURAN (Kajian Dalam Tafsir Al Azhar) - Syahril Amri Hasibuan, Syamsu Nahar, Zulheddi (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: This study aims to analyze: 1) Opinion of mufassir about the values of the educator’s socialcompetency in the interpretation of Al-Azhar, 2) About the Indicator of the educator’s social competencywhich are found in the Qur’an Surah Al Hujurat study in the commentary of Al-Azhar. And 3) Therelevance of the educator’s social competency in the Qur’an and the Law on Teachers and lecturers inforce today. This research is a library research (library research), with the tahlili method because all that isexcavated is sourced from literature. The results of the study show that: 1) the opinions of the commentatorson the values of social competence of educators in the Qur’an. 2) Indicator of the social competenceof educators in QS Al Hujurat (study in Al Azhar interpretation) is the first Adab manners in speaking,Procedures for interacting with the community, Applying the principle of true brotherhood and the spirit oftogetherness both within the school and in the wider community, and being able to avoid bad prejudicesto others, and sharing with others. 3) the values of the social competence of educators contained in theKoran are still relevant to the current law in terms of increasing the professionalism of educators.Penelitian ini bertujuan untuk menganalisis: 1) Pendapat para mufassir tentang nilai-nilai kompetensisosial pendidik yang terdapat dalam Alquran Surah Al Hujurat kajian dalam tafsir Al-Azhar. 2) TentangIndikator kompetensi sosial pendidik yang terdapat dalam Alquran Surah Al Hujurat kajian dalam tafsirAl-Azhar. Dan 3) Relevansi kompetensi sosial pendidik dalam Alquran dan Undang-undang tentang Gurudan dosen yang berlaku saat ini. Penelitian ini merupakan penelitian kepustakaan (library research),dengan metode tahlili karena semua yang digali adalah bersumber dari pustaka. Hasil penelitian menunjukkanbahwa: 1) pendapat-pendapat para mufassir tentang nilai-nilai kompetensi sosial pendidik dalam Alquran.2) Indikator kompetensi sosial pendidik dalam Qs Al Hujurat (kajian dalam tafsir Al Azhar) adalahpertama Adab sopan santun dalam berbicara, Tata cara berintraksi dengan masyarakat, Menerapkanprinsip persaudaraan sejati dan semangat kebersamaan baik dilingkungan sekolah maupun di masyarakatluas, serta mampu menghindari prasangka yang buruk kepada orang lain, dan saling berbagi terhadapsesama. 3) nilai-nilai kompetensi sosial pendidik yang terdapat dalam Alquran masih relevan denganUndang-undang yang berlaku saat ini dalam hal meningkatkan profesionalisme pendidik.Kata Kunci; Kompetensi Sosial, Pendidik dan Tafsir